تعدد الأصوات في رواية توابل المدينة للروائي حميد عبد القادر - عماري, هدى (جامعة الوادي - University of Eloued, 2023)
شكل تعدد الأصوات ظاهرة في الخطابات الروائيّة، وكان محل اهتمام الروائيين؛ لأنّه يمنح الروائي حريةً لتقديم الشّخصيات ويمكنه من عرض إيديولوجيتها، وتقديم توجهها الفكريّ من منظورات سرديّة وزوايا نظر عديدة . يهدف البحث إلى كشف تعدد الرواة في أنموذجٍ من الخطاب الروائيّ الجزائريّ المعاصر. وقد وقع اختيارنا على رواية توابل المدينة للروائيّ الجزائريّ حميد عبد القادر؛ لأنّها رواية تستجيب لمتطلبات البحث من جهة، وتتجاوز الرؤية السّرديّة الأحادية من جهة أخرى، إذ يمكن إدراجها ضمن الرواية البوليفونية. لتصل الدارسة إلى نتائج أهمها أن توابل المدينة رواية تجسد التعدد اللّغويّ، عرضت المادة الحكائية وفق مبدأ الحوارية. وتناوبت فيها الأصوات على السّرد من خلال استخدام الضمائر السردية المتكلم، المخاطب، الغائب، وبذلك قدمت منظورات مستقلة ساهمت مجتمعة في بلورة رؤية الروائي للواقع . Polyphony was a phenomenon in narrative discourses and was of interest to novelists because it gives the novelist the freedom to present characters and be able to present their ideology, and present their intellectual orientation from narrative perspectives and many points of view. The research aims to explore the multiplicity of narrators in a model of Algerian novelist discourse. We chose the novel Spice of the City by the Algerian novelist Hamid Abdelkader, because it responds to the requirements of research on the one hand, and goes beyond the monolithic narrative vision on the other, as it can be included in the polyphonic novel. To reach the most important results of the study that the spices of the city is a novel that embodies multilingualism, presented the narrative material according to the principle of dialogue. The voices alternated on the narrative through the use of narrative pronouns speaker, addressee, absent, and thus provided independent perspectives that collectively contributed to the crystallization of the novelist's vision of reality.
Article
Keywords: الرواية الجزائرية ; تعدد الأصوات ; السّارد ; الحوار ; الشخصية الروائية.